Rubella igg antibody among Nigerian pregnant women without vaccination history (2013)
"Rubella is a vaccine-preventable viral infection, its aetiologic agent; rubella virus was identified as human teratogen capable of causing a spectrum of birth defects described as congenital rubella syndrome (CRS). Despite the availability of safe and effective vaccines, significant proportion of the population remains susceptible to rubella infection in developing countries. More significantly, such developing countries including Nigeria have not demonstrated adequate commitment to preventive vaccination; a panacea for intervention. Consequently, this study was designed to determine the prevalence of anti-rubella IgG among pregnant women to ascertain the proportion of susceptible population. A total of 273 consenting rubella vaccine naïve antenatal clinic attendees aged 15-42 years (Median age = 28 years) were randomly selected and their sera analyzed for qualitative and quantitative anti-rubella IgG detection. Overall, 244/273 (89.4%) pregnant women enrolled in this study had protective level (Titre = >10 IU/mL) of anti-rubellaIgG (Median Titre = 165 IU/mL; Range = <10 - >250 IU/mL), while, 29/273 (10.6%) of the study population lack protective antibody titre ( OD = <10 IU/mL). Results confirm previous reports of exposure, infection, and continuous circulation of rubella virus in Nigeria. It emphasizes the need for improved and continuous surveillance for rubella and CRS cases, prompt vaccination of vulnerable populations, and evaluation of health policies to achieve immunization and ultimately ensure control/elimination of rubella virus in Nigeria and beyond."